2018
DOI: 10.1016/j.conb.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic strategies to tackle neurological diseases in fruit flies

Abstract: Drosophila melanogaster is a genetic model organism that has contributed to the discovery of numerous genes whose human homologues are associated with diseases. The development of sophisticated genetic tools to manipulate its genome accelerates the discovery of the genetic basis of undiagnosed human diseases and the elucidation of molecular pathogenic events of known and novel diseases. Here, we discuss various approaches used in flies to assess the function of the fly homologues of disease-associated genes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 71 publications
0
49
0
Order By: Relevance
“…45,46 Later, the D. melanogaster model was used to expand this theory to include that lifespan is both heritable and plastic. 4 Normal aging has also been studied at the genome-wide level. 13,[51][52][53][54] Despite the lack of a closed circulatory system, even tissues such as heart muscle change with age in a similar manner as human cardiac aging.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Later, the D. melanogaster model was used to expand this theory to include that lifespan is both heritable and plastic. 4 Normal aging has also been studied at the genome-wide level. 13,[51][52][53][54] Despite the lack of a closed circulatory system, even tissues such as heart muscle change with age in a similar manner as human cardiac aging.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 99%
“…These D. melanogaster models of neurodegenerative disease have assisted our understanding of neurodegenerative pathology, and also facilitate high-throughput screening for disease modifiers that can be translated into better therapeutics. 4 Normal aging has also been studied at the genome-wide level. The study of the transcriptome of 14 different Drosophila species with varied life-span suggested additive small effects of many genes, instead of strong effect of a few.…”
Section: Drosophila Melanogaster In Aging Studiesmentioning
confidence: 99%
“…However, none of these variants have been modeled in vivo in part, due to a gap in our understanding of the function of TAFs during brain development. By demonstrating that TAFs are required for NSC cell cycle progression, NSC cell polarity, and act to prevent premature differentiation while not affecting survival, our work provides a foundation for future studies aimed at uncovering the causative variants in these disorders (55).…”
Section: Cells (Escs) As Inducible Depletion Of Taf8 Resulted In Escmentioning
confidence: 86%
“…This provides a means for rigorous quality assessment of the genetic reagent and, when combined with mutant and/or truncated forms of the UAS-GOI cDNA, facilitates structure-function analysis. In addition, a UAS-human-homologue cDNA of the GOI permits humanization of the flies and assessment of human variants (Bellen and Yamamoto, 2015;Kanca et al, 2017;Şentürk and Bellen, 2018;Chao et al, 2017;Yoon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%